The Impact of Oil Revenues on the Budget Deficit Public Opinion In Iraq for the Period 2005-2025 - saif Al-Ramli; Yahya Al-Bayati (Journal of Macroeconomics and Social Development, 2026)
The current research aims to analyze the impact of oil revenues on the Iraqi budget deficit during the period 2005–2025. This is achieved by examining the relationship between fluctuations in oil prices and oil revenues, on the one hand, and the level of the budget deficit, on the other. The research also seeks to identify the implications of this relationship on public opinion regarding the management of public financial resources in Iraq. The Iraqi economy is a rentier economy, and its public revenues are heavily dependent on oil. The hypotheses section outlines the analytical methodology described above. Subsequent hypothesis testing relies on annual time series data for the two variables. Standard and statistical methods, such as normative tests, are used to determine the characteristics of the relationship between them, thus establishing the relationship between the two variables. The research findings indicate a strong inverse relationship between oil revenues and the Iraqi budget deficit. Furthermore, higher oil revenues lead to a lower budget deficit, and vice versa. Given the Iraqi budget's heavy reliance on oil, fluctuations in oil prices and production negatively impact the budget. Consequently, when oil prices decline or production decreases, the budget deficit increases. Furthermore, statistical analysis shows that oil revenues contributed significantly to the budget deficit variance during that period. The research indicates the need to diversify public revenue sources, support a stronger role for non-oil sectors, rationalize public spending, and establish medium-term fiscal frameworks to mitigate budget deficit volatility and enhance fiscal sustainability. The research also recommends creating financial stabilization funds to mitigate the impact of oil price shocks on the budget.